Evaluation of Three Breeding Cycles for Seedling Weight of Switchgrass, Big Bluestem, and Indiangrass. Issue 4 (1st July 2014) - Sebolai, Boingotlo; Vogel, Kenneth P.
ABSTRACT: A modified form of restricted, recurrent phenotypic selection was used to select for seedling shoot weight in switchgrass ( Panicum virgatum L.), big bluestem ( Andropogon gerardii Vitman), and indiangrass [ Sorghastrum nutans (L.) Nash] populations for three generations. Seedlings were grown in micropots in trays in a greenhouse and were individually clipped and weighed 4 wk after emergence. The seedlings were allowed to regrow, and the heaviest seedlings were transplanted to field nurseries for polycrossing to produce Syn 1 seed. Three breeding cycles were conducted for each grass. After the third breeding cycle, Syn 2 generation seed was produced for each cycle, including cycle 0 for 2 yr, and was used in subsequent greenhouse and field evaluations to determine if the breeding procedure improved seedling vigor as measured by seedling shoot weight. In two greenhouse evaluation trials, the increase in seedling weight per cycle was 7.8, 5.6, and 10.2% for big bluestem, switchgrass, and indiangrass, respectively. In two field trials, seedling weight also increased with successive cycles of selection except for indiangrass in one trial. Establishment success as measured by stand counts did not differ among the cycles of selection for the three grasses in the field trials. Based on these results and the results of subsequent breeding and field evaluation work on seedling tiller number, it is apparent that seedling traits of these grasses can be modified by breeding. To improve establishment of these grasses, research on developing agronomic seed production practices that result in improved seed quality would also be beneficial.